1997
DOI: 10.1002/hep.510250626
|View full text |Cite
|
Sign up to set email alerts
|

Targeted nucleotide exchange in the alkaline phosphatase gene of HuH-7 cells mediated by a chimeric RNA/DNA oligonucleotide

Abstract: Although a variety of methods has been devised for modification of hepatic genes, none has been effective for long-term correction of genetic disorders. In this study, we employed a recently described novel experimental strategy for site-directed nucleotide exchange in genomic DNA of HuH-7 human hepatoma cells. A chimeric 2'-O-methylated-RNA/DNA oligonucleotide containing sequences complementary to 25 bases of the alkaline phosphatase gene was constructed as a duplex containing a G to A substitution at nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 33 publications
3
97
1
1
Order By: Relevance
“…135 Chimeraplasty was originally performed on episomal targets, 136 the sickle cell mutation in cultured lymphoblasts, 137 cell-free extracts, 138 and a variety of cultured cells, 139,140 including HuH-7 cells for the endogenous alkaline phosphatase gene. 141 To increase hepatocyte uptake, chimeric molecules were either complexed with lactosylated PEI or encapsulated with anionic, cationic, or neutral liposomes containing galactocerebroside for targeting to the asialoglycoprotein receptor. Delivery was assessed by confocal microscopy, and single base correction rates by polymerase chain reaction (PCR)/filter lift hybridizations.…”
Section: Gene Repair Strategiesmentioning
confidence: 99%
“…135 Chimeraplasty was originally performed on episomal targets, 136 the sickle cell mutation in cultured lymphoblasts, 137 cell-free extracts, 138 and a variety of cultured cells, 139,140 including HuH-7 cells for the endogenous alkaline phosphatase gene. 141 To increase hepatocyte uptake, chimeric molecules were either complexed with lactosylated PEI or encapsulated with anionic, cationic, or neutral liposomes containing galactocerebroside for targeting to the asialoglycoprotein receptor. Delivery was assessed by confocal microscopy, and single base correction rates by polymerase chain reaction (PCR)/filter lift hybridizations.…”
Section: Gene Repair Strategiesmentioning
confidence: 99%
“…This study provided the basis for subsequent applications of RDO for conversion of chromosomal genes. Since then, site-specific chromosomal corrections or mutations have been reported in several genes (13)(14)(15)(16)(17)(18)(19)(20)(21). An RDO was shown to induce a sequence-specific mutation in the factor IX gene in cell culture and in vivo by intravenous injection (19).…”
Section: Application Of Rdo In Mammalian Cellsmentioning
confidence: 99%
“…These results demonstrated the generality for a targeted sequence in vitro and in vivo by a double-stranded RDO. However, most previous studies detected the gene conversion event by PCR amplification of genomic DNA without direct confirmation at the protein level (13)(14)(15)(16). Concerns have been raised about potential artifacts during PCR amplification, or by cross-contamination between cells, especially because no clonal analysis has been performed (33,34).…”
Section: Application Of Rdo In Mammalian Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 This novel approach of gene repair, based on in vitro experimental evidence, was shown by Yoon et al 11 and Cole-Strauss et al 12 to be capable of introducing targeted single base conversions in episomal and genomic DNA in cultured cells. We then reported that the chimeraplast technology could introduce a missense mutation in genomic DNA in human hepatoma cells, 13 and nonreplicating isolated rat hepatocytes. 14 The high rates of nucleotide conversion observed in primary hepatocytes resulted, in part, from significantly improved delivery of chimeraplasts using our modified nonviral-ASGPR receptor targeted delivery systems.…”
mentioning
confidence: 99%